2014
DOI: 10.1149/06403.0973ecst
|View full text |Cite
|
Sign up to set email alerts
|

Performance of the High Temperature PEM Membrane Electrode Assembly

Abstract: This communication will provide details on some of the high temperature polymer electrolyte membrane (HT-PEM) membrane-electrode-assembly (MEA) performance targets most recently achieved by Danish Power Systems. These include (i) MEA performances of >0.67 V at 0.2 A cm-2 using dry H2/Air, (ii) MEA lifetime of 12000 h at 0.23 A cm-2 using dry H2/Air with an average degradation rate of 9 µV h-1, and (iii) an integrated 5 kW stack/reformer system using methanol reformate as fuel. Studies using reformate have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…These results verified the same tendency as the previously reported in ECS Transactions 11, 15 for the improvement of the MEA and the anode for HT‐PEMFC.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These results verified the same tendency as the previously reported in ECS Transactions 11, 15 for the improvement of the MEA and the anode for HT‐PEMFC.…”
Section: Discussionsupporting
confidence: 92%
“…H 3 PO 4 ‐doped polybenzimidazole (PBI) as the electrolyte membrane has been demonstrated to be the most successful electrolyte system for high‐temperature operation 11, 12. In a recent publication, Kerr et al 11 demonstrated that these membranes operated well with low humidification during a test performed over 10,000 hours.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover the influence of Pt activation on the corrosion of carbon in gas diffusion electrodes was investigated using differential electrochemical mass spectroscopy [5]. In a HT-PEMFC a phosphoric-acid-doped polybenzylimidazole (PBI) membrane for the ionic exchange of protons has been demonstrated to be the most successful electrolyte system for high-temperature operation [6]. Considering this, the evaluation of the corrosion of Pt-based electrocatalysts in two different supports under HT-PEMFC conditions in the potential window between 0.0 V (vs. RHE) and 1.0 V (vs. RHE) will be evaluated in this paper.…”
Section: Introductionmentioning
confidence: 99%